Dissociative symptoms predict risk for the development of PTSD: Results from the National Health and Resilience in Veterans Study (NHRVS). (December 2020) - Herzog, Sarah; Fogle, Brienna M.; Harpaz-Rotem, Ilan; Tsai, Jack; DePierro, Jonathan; Pietrzak, Robert H.
Abstract: Dissociative symptoms following trauma exposure, such as derealization (i.e., feeling that one's experience is strange and unreal) and depersonalization (i.e., feeling detached from oneself) have been implicated in the development and maintenance of posttraumatic stress disorder (PTSD). In the current study, we analyzed data from a 3-year prospective cohort study of a nationally representative sample of U.S. veterans to examine whether trait dissociative symptoms, which may impair adaptive emotion regulation following trauma exposure, predict risk for the development of PTSD in trauma-exposed veterans. Results revealed that derealization symptoms predicted a nearly 5-fold increase in relative risk of incident PTSD (relative risk ratio = 4.57, 95% confidence interval = 1.55–13.52), even after adjusting for relevant sociodemographic and trauma-related factors, and severity of PTSD symptoms at baseline. To our knowledge, this study is the first to suggest that trait dissociative symptoms—specifically derealization—may be an important population-based risk factor for the development of PTSD in trauma-exposed U.S. military veterans. These findings add to a body of literature on the prediction of PTSD that largely focuses on stable or immutable risk factors such as sociodemographic and trauma characteristics, or peritraumatic emotional reactions, and underscores the potential clinical utility of assessing, monitoring, and treating derealization symptoms in trauma-exposed U.S. military veterans at risk for PTSD.